EFL TEACHERS’ ATTITUDES TOWARD INTERCULTURAL COMMUNICATIVE COMPETENCE: A SYSTEMATIC REVIEW OF CHALLENGES AND PEDAGOGICAL IMPLICATIONS - Beazidou, Eleftheria; Tsatzali, Katerina; Stavropoulou, Georgia (LLT Journal: A Journal on Language and Language Teaching, 2025)
This study systematically reviews EFL teachers’ attitudes toward integrating intercultural communicative competence (ICC) in English language teaching, focusing on the gap between their positive perceptions and actual classroom practices. Thirty studies published between 2014 and 2024, representing diverse educational contexts, were analyzed in accordance with PRISMA guidelines. The findings show that although EFL teachers globally acknowledge the importance of ICC, its practical implementation varies significantly. Influencing factors include limited understanding of ICC, deeply rooted linguistic priorities, inadequate professional development, rigid curricula, lack of authentic teaching materials, and time constraints. Despite these challenges, several studies report that teachers who actively integrate ICC employ practices such as the use of authentic cultural materials, critical discussions on cultural stereotypes, project-based intercultural activities, and comparisons between students’ own cultures and those of English-speaking contexts. However, these practices remain sporadic and largely depend on individual initiative rather than systemic support. The review highlights the need for targeted teacher professional development, flexible curricula, the development of intercultural teaching resources, and opportunities to enhance learners’ active participation. These measures are essential for bridging the gap between beliefs and practice, fostering learners’ ICC, and promoting a more inclusive and globally responsive approach to English language education.